Bambara Nut Root-Nodules Bacteria from a Semi-Arid Region of South Africa and Their Plant Growth-Promoting Traits - Ayangbenro, Ayansina Segun; Adem, Mohomud Rashid; Babalola, Olubukola Oluranti (International Journal of Microbiology, 2023)
Rhizobial nitrogen-fixing bacteria are the main inhabitants of the root nodules of legume plants. Studying the bacterial community of legume nodules is important in understanding plant growth and nutrient requirements. Culture-based technique was used to examine the bacterial community of these underground organs from Vigna subterranea L. Verdc (Bambara nut), an underutilized legume in Africa, for plant growth-promoting traits. In this study, Bambara nuts were planted to trap root-nodule bacteria, and the bacteria were morphologically, biochemically, and molecularly characterized. Five selected isolates were screened in vitro for their plant growth-promoting traits and exhibited differences in their phenotypic traits. The polymerase chain reaction (PCR) products were subjected to partial 16S rRNA gene sequencing for phylogenetic analysis. Based on 16S rRNA gene sequence, the isolates were identified as BA1 (Stenotrophomonas maltophilia), BA2 (Chryseobacterium sp.), BA3 (Pseudomonas alcaligenes), BA4 (Pseudomonas plecoglossicida), and BA5 (Pseudomonas hibiscicola). Results showed that four of the five isolates could produce IAA. The capability to solubilize phosphate in Pikovskaya’s agar plates was positively shown by four isolates (BA2, BA3, BA4, and BA5). Three isolates could produce hydrogen cyanide while isolates BA1, BA3, BA4, and BA5 were found to have ammonia-production traits. The results suggest that these plant growth-promoting isolates can be used as inoculants for plant growth and productivity.